(untitled) - Winfried Karl Grassmann (New Jersey, 1996)
Propositional calculus; Predicate calculus; Induction and recursion; Prolog; Sets and relations; More about functions; Graphs and trees; Formal requirement specification in Z; Program correctness proofs; Grammars languages, and parsing; Derivations; An overview of relational database systems.
Keywords: Computer science - mathematics